Navigating Educational Quality in the New Normal: Strategic Adaptation through a Five-Stage Internal Audit Framework for Higher Education Resilience - Eko Nurhaji Purnomo; Abdur Rofik; suwadji (RAHMATAN LIL ALAMIN: Journal of Peace Education and Islamic Studies, 2025)
The post-pandemic "new normal" era necessitates a transformation in higher education governance to maintain educational quality, particularly through internal oversight mechanisms. This study aims to explore adaptive internal audit strategies in response to the dynamics of this disruptive era. Employing a qualitative-interpretative approach, this case study was conducted at STIAMAK Barunawati Surabaya. Data were gathered through in-depth interviews with the Head of the Internal Quality Assurance Unit and task force members, subsequently analyzed using inductive techniques to derive substantive theories. The findings formulate a five-stage internal audit framework: (1) adaptive planning, (2) digital document auditing, (3) limited on-site inspection, (4) technology-based interview confirmation, and (5) virtual closing meetings. The results indicate that most audit stages have been successfully transitioned to remote execution through technological integration, although physical inspections persist due to efficiency considerations and technical infrastructure constraints. This study provides a practical contribution as a reference for auditors to enhance the effectiveness of remote auditing, ensuring the resilience of higher education quality in the future.